Experimental study on catenary action of RC beam-column subassemblages - Yu, Jun (2013)
Catenary action is considered as the last defense of a structure to mitigate progressive collapse, provided that the remaining structure after an initial damage can develop alternate load paths and a large deformation has occurred in the affected beams and slabs. As a result, catenary action requires high continuity and ductility of joints. To investigate whether current RC structures designed according to ACI 318-05 could develop catenary action under column removal scenarios, two one-half scaled beam-column sub-assemblages with seismic and non-seismic detailing were designed and tested to complete failure, i.e. rebar fracture. The sub-assemblage consists of two end column stubs, a two-bay beam, and one middle beam-column joint at the junction of two single-bay beams. To ensure sufficient horizontal resistance, the sizes of end columns were enlarged to be rather stiff. To simplify the boundary conditions in the first batch of tests of our ongoing project and to make the test system statically determinate, two end column stubs were supported onto two horizontal restraints and one vertical restraint to simulate the encased supports. A concentrated load was applied vertically by a hydraulic actuator on the top of the middle joint using displacement control until the whole system eventually failed. The loading rate was controlled manually to simulate quasi-static structural behavior. The study provided insight not only into catenary action of sub-assemblages, but also the performance and failure mode of the middle joints, as well as the influence of two different detailing requirements. During the whole loading history, the cross-sectional internal forces at any beam locations can be evaluated according to the measured reaction forces. Finally, a simple analytical model will be used to check the mechanism of catenary action.